De-noising algorithms for the raised cosine pulse signal using the minimum-energy frame in the discrete signal space - Ying-hai XIE; Wei YANG; Ting-ting FAN (Tongxin xuebao)
The de-noising algorithms were proposed for the raised cosine pulse signal using minimum-energy(wavelet) frame in the discrete signal space.For the given two minimum-energy frames,the decomposition coefficients of sampled sequence appeared significant statistical characteristics difference between the raised cosine pulse signal and additive Gaussian noise under the frames’sub-sequences.Based on this,two threshold de-noising algorithms were provided to makes full use of the merit that the frame was fit for the de-noising work,they removed partial noise component while keeping the component of original signal and got effic nt de-noising result.The simulation results show that,when the modulating method is BPSK and its raised cosine pulse signal is polluted by the additive Gaussian noise,then if add a pre-processing link to denoise the receiving waveform using the algorithms,the receiver can greatly increase the signal-to-noise ratio of receiving signal and have about 3.1dB and 2.7dB performance gain of bit error ratio,respectively.